Philosophical reflexivity and entrepreneurship research - Fayolle, Alain; Ramoglou, Stratos, 1980-; Karataş-Özkan, Mine; Nicolopoulou, Katerina (Routledge rethinking entrepreneurship research., 2018)
Entrepreneurship research attracts scholars from a wide spectrum of disciplines. Yet the field is multi-paradigmatic and lacking consensus, even on the nature of core entrepreneurial phenomena. What is recognized is that it is characterized by dynamic and emergent processes - a complex interplay between actors, processes and contexts. As a result, post-positivistic approaches are gaining traction in a field long dominated by positivistic philosophies. This book reflects on the fundamental philosophical basis of entrepreneurship scholarship. It explores the shifting meanings of entrepreneur and entrepreneurship, the unexamined assumptions which lie behind the established discourses which legitimize or dismiss the possibilities for scholarship. Contributing scholars adopt a reflexive approach to entrepreneurship research challenging readers to question their approaches and assumptions and explicitly defend them against competing alternatives. Building on this critical reflection, this book provides space for philosophical reflexivity in the conduct and publication of scholarly enquiry and will be of great interest to scholars, researchers and advanced students in all aspect of entrepreneurship study.